HER-2/neu over expression in gall bladder adenocarcinoma: A quest for potential therapeutic target - Pragya Jain; Surbhi Goyal; Geeta Chauhan; Kaushik Majumdar; Shahajad Ali; Puja Sakhuja; Anil K Agarwal (Indian Journal of Pathology and Microbiology, 2020)
Background: Gall bladder carcinoma (GBC) is an aggressive malignancy with high mortality and aggressive course, with palliation as the only available option. Objectives: To evaluate frequency of HER-2/neu overexpression in GBC and to seek its correlation, if any with conventional clinicopathological parameters and survival. Methods: Immunohistochemistry (IHC) was performed on 200 cases of GBC, 32 cases of dysplasia, and 100 cases of chronic cholecystitis. Fluorescent in situ hybridization (FISH) was performed on 30 randomly selected cases of GBC to validate IHC. HER-2/neu overexpression (IHC 3+/FISH amplification ≥2.2) was correlated with clinicopathological parameters by Chi-square test.P <0.05 was considered significant. Survival analysis was done by log-rank test and Kaplan-Meier analysis. Results: HER-2/neu overexpression was seen in 14% (28/200) GBC cases but was not found in dysplasia and chronic cholecystitis. Majority of these cases were ≤grade 2 and in advanced stage, however this was not statistically significant. A lower mean survival in HER-2/neu positive group as compared to HER-2/neu negative group (17.1 ± 2.3 month versus 67.6 ± 8.5 month, respectively) was observed. Concordance between IHC and FISH was seen in 18/19 cases. Conclusion: This study delineates a subset of GBC patients with HER-2/neu overexpression, in whom targeted therapy can offer a survival benefit.